Wishmaster - Kurtzman, Robert; Divoff, Andrew; Chris Lemmon; Robert Englund; Tammy Lauren (USA Pierre David, 1997)
In the beginning of time, two forms of life were first created. One were the Angels and the other were the Djinn, a race of beings bent on humanity's destruction and ruling Earth. But the Djinn can only take over when one of their own grants three wishes to the person who wakes him. And the Djinn has a way to turn one's wildest dreams into their worst nightmare. In 1997, when a statue carrying the jewel that holds a Djinn hostage is destroyed, a young gemologist (Tammy Lauren) accidently wakes the Djinn (Andrew Divoff) and releases him into the world where he can complete his hellish mission. But can she figure out the perfect wish that will banish the Djinn forever and save humanity?
A demonic djinn attempts to grant its owner three wishes, which will allow him to summon his brethren to earth.
Peter Atkins
Language(s): English Subtitle(s): No Subtitle
Keywords: Horror; Fantasy